1995
DOI: 10.1098/rstb.1995.0005
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the four-way DNA junction and its interaction with proteins

Abstract: The four-way DNA junction is an important intermediate in recombination processes; it is, the substrate for different enzyme activities. In solution, the junction adopts a right-handed, antiparallel-stacked X-structure formed by the pairwise coaxial-stacking of helical arms. The stereochemistry is determined by the juxtaposition of grooves and backbones, which is optimal when the smaller included angle is 60 degrees. The antiparallel structure has two distinct sides with major and minor groove-characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 46 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In low ionic strength solutions (≤ 100 μM Mg +2 ), the open-x or unstacked conformer is favored 2228 . In high ionic strength solutions (≥ 100 μM Mg +2 ), the helical arms of each duplex stack coaxially to generate a cruciform or stacked-x structure 2831 . Several research labs have confirmed that the stacked-x conformer possesses greater structural heterogeneity than the open-x conformer; these studies show that the stacked-x conformer can fold into the two isomers (I/II and III/IV) displayed in Figure 1B 3235 .…”
Section: Introductionmentioning
confidence: 99%
“…In low ionic strength solutions (≤ 100 μM Mg +2 ), the open-x or unstacked conformer is favored 2228 . In high ionic strength solutions (≥ 100 μM Mg +2 ), the helical arms of each duplex stack coaxially to generate a cruciform or stacked-x structure 2831 . Several research labs have confirmed that the stacked-x conformer possesses greater structural heterogeneity than the open-x conformer; these studies show that the stacked-x conformer can fold into the two isomers (I/II and III/IV) displayed in Figure 1B 3235 .…”
Section: Introductionmentioning
confidence: 99%